KARAKTERISTIK PENDERITA TB PARU DENGAN EFUSI PLEURA RAWAT INAP DI RUMAH SAKIT UMUM SANTA ELISABETH MEDAN TAHUN 2011–2016 - Riance Maria Sinaga; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Pulmonary TB is on the second ranks after HIV as the main causes of death in global. Pulmonary TB is a contagious diseases that caused by Mycobacterium tuberculosis. Patients with pulmonary TB could have complication, and one of the complications is Pleural Efusion. This study aims to provide description about the characteristics of pulmonary tuberculosis with pleural effusion on hospitalizesd patients at Santa Elisabeth General Hospital Medan in 2011-2016. This study is decriptives by using case series design. The sample population was all pulmonary tuberculosis with pleural effusion on hospitalizesd patients which was 71 cases. The data analysis uses a secondary data by using Chi-Square and Fisher’s Exact. The results of this study showed the highest proportion of hospitalized pulmonary TB patients with pleural effusion at the aged of >50 years old is male 61%, self-employed (39%), outside of area Medan (61%), dyspnea (74,6%), unilateral (86%), without comorbid (54,9%), average length of stay is 7 days, fully recovered (57,1%). There are no significant differences between the age with sexes (p=0,561), age with location of fluid (p=0,514), sexes with location of fluid (p=0,296), comorbid with location of fluid (p=0,330). It is expected for patients to consume drugs regularly to prevent further illness. For Santa Elisabeth Hospital Medan to increase the completeness of patients medical record. Keywords : Pulmonary TB, Pleural Effusion, Santa Elisabeth Hospital Medan